Orang Asli Health and Lifeways Project (OA HeLP) : a cross-sectional cohort study protocol - Ian J., Wallace; Amanda J., Lea; Yvonne A., L. Lim; Steven K., W. Chow; Izandis, Mohd Sayed; Romano, Ngui; Mohd Tajudin, Haji Shaffee; Ng, Kee Seong; Colin, Nicholas; Vivek V., Venkataraman; Thomas S., Kraft (BMJ Publishing Group Ltd, 2022)
Introduction Non-communicable disease (NCD) risk is influenced by environmental factors that are highly variable worldwide, yet prior research has focused mainly on high-income countries where most people are exposed to relatively homogeneous and static environments. Understanding the scope and complexity of environmental influences on NCD risk around the globe requires more data from people living in diverse and changing environments. Our project will investigate the prevalence and environmental causes of NCDs among the indigenous peoples of Peninsular Malaysia, known collectively as the Orang Asli, who are currently undergoing varying degrees of lifestyle and sociocultural changes that are predicted to increase vulnerability to NCDs, particularly metabolic disorders and musculoskeletal degenerative diseases.